Agri-food System and Climate Change: A Focus on Agroecology and Regenerative Agriculture Approaches - Aguilar , Giselle; Paulino, Sonia (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The future of global food security depends on an agri-food system (AFS) that is currently under direct threat from climate change. This system, essential for sustaining the world population, faces challenges that jeopardize both its functionality and sustainability. The AFS, often cited as one of the primary contributors to climate change, is also found to be highly vulnerable to its impacts. In light of this reality, sustainable and resilient alternatives are increasingly necessary. There exists a knowledge gap regarding the possibilities of transforming the AFS in alignment with climate resilience. What aspects are highlighted to understand the role of alternative approaches, agroecology, and regenerative agriculture (RA) in the reconfiguration of the agri-food system (AFS) in the context of the challenges posed by climate change? This paper aims to address this question by elucidating the main aspects of these approaches. A systematic literature review is conducted in the Web of Science and Scopus databases, followed by a SWOT analysis (strengths, weaknesses, opportunities, and threats). The key aspects identified in the review include: productive practices, actors, benefits, and challenges. Among the strengths, sustainable productive practices and the diversity of actors promoting these approaches stand out. The weaknesses include barriers to implementation and the lack of concrete evidence regarding their effectiveness in mitigating climate change. However, the need to expand the production of scientific evidence presents an opportunity. The threats are related to political barriers to the dissemination of agroecology and the lack of consensus on RA techniques.